OPTIMALISASI PENGELOLAAN DATA PTK BERBASIS SIMPEG DAN DAPODIK DI DINAS PENDIDIKAN KOTA PALANGKA RAYA - Muhammad Ramadhan; Slamet Riyadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze and optimize the management of Educators and Education Personnel (PTK) data based on the Personnel Management Information System (SIMPEG) and the Basic Education Data (Dapodik) at the Palangka Raya City Education Office. The phenomenon underlying this study is the suboptimal integration between the two systems, which results in duplication, inconsistency, and delays in updating personnel data. This study uses a descriptive qualitative approach, with data collection techniques including in-depth interviews, participatory observation, and document studies. Data analysis is conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions.The research results indicate that the management of teacher and education personnel (PTK) data at the Palangka Raya City Education Office is still carried out partially between SIMPEG and Dapodik, with the main obstacles being limitations in technological infrastructure, operator competence, and the absence of standardized data integration procedures. Nevertheless, various optimization efforts have been undertaken through human resource competency improvement training, the development of web service-based integration systems, and the implementation of tiered data verification and validation (verval) mechanisms. These efforts successfully increased the data conformity rate between SIMPEG and Dapodik from 63% in 2023 to 87% by mid-2025.The findings of this study indicate that the success of optimizing PTK data management is highly determined by the balance between technology readiness, organizational capacity, and local government policy support, as explained in the Technology-Organization-Environment (TOE) framework. In addition to providing practical benefits in improving the efficiency and transparency of educational bureaucracy, the results of this study also support the implementation of the one education data policy in accordance with the mandate of Presidential Regulation Number 39 of 2019 on One Data Indonesia. Therefore, it is recommended that the Palangka Raya City Government formulate specific regulations on integrated education data management and expand digital training for school operators and Education Office staff.